Methodology of teaching the techniques of playing volleyball among 11-12 year-old boys - Lazunina, I.; Kosheleva, M. (BIO Web of Conferences, 2020)
In all games, connected with the ball, main attention of a player should be paid to a moving ball. This rule ignoring leads to often inaccurate ball hitting. Admittedly, players should be taught to observe the opponent. But at the same time direct observation is held to the definite limit. And during the moment of direct training and hit fulfillment main attention is paid to the ball and other environment is observed only with the help of peripheral vision. During the game young volleyball players lose many favorable moments only because they can`t choose the best ways of a hit in the combat with the opponent. During the playing technique explanation and study it is necessary to study thoroughly the basis of the technique, the sequence of the separate body parts movements, speed and their amplitude during different techniques fulfillment. These factors are the main for volleyball player`s actions effectiveness achievement. While the attacking hit fulfillment and blocking it is important to control the opponent during the technique fulfillment. That is why it is necessary to master the ability to observe the opponent`s movements all the time, till the hit on the ball, among young volleyball players.